If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+5)/6=2
We move all terms to the left:
(x+5)/6-(2)=0
We multiply all the terms by the denominator
(x+5)-2*6=0
We add all the numbers together, and all the variables
(x+5)-12=0
We get rid of parentheses
x+5-12=0
We add all the numbers together, and all the variables
x-7=0
We move all terms containing x to the left, all other terms to the right
x=7
| 9m=67 | | q+-72=-27 | | 14x+5+21x=180 | | 2x1=x+13 | | -3x(-4-2x)=-2+x-1) | | 8÷x+8=5÷8 | | 64=-3(8+6r)-(r+7) | | 7r+2=3r-26 | | -6c+-4c=-6 | | 3x+15=5x-21 | | |0.5x+3|=x^2-4 | | 3x+2+5x-14=90 | | |0.5x+3|=x^2=4 | | 5(2x-7)=6(x+3) | | -8x-36=3x-7(4x-7) | | 1+4x=2+3.75x | | 2x-12=2x+5 | | 4y+53=57 | | 4(-3y+10)=100 | | x3+7=12x= | | 68=8h | | 5x7x15=19 | | 3-x=22-7x | | 3x+8x-19=58 | | 8-6x+15=2x21 | | v/5+8=11 | | 18−5w+7w−4=28 | | 3+(1/4)a=3 | | 59=n+31 | | 3d+6=6d | | -8=3k-4/3(-3k+6) | | 2x+7-x=1 |